2007
DOI: 10.1590/s0100-879x2007000600018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of He-Ne laser therapy on the dynamics of wound healing in mice treated with anti-inflammatory drugs

Abstract: We determined the effects of helium-neon (He-Ne) laser irradiation on wound healing dynamics in mice treated with steroidal and nonsteroidal anti-inflammatory agents. Male albino mice, 28-32 g, were randomized into 6 groups of 6 animals each: control (C), He-Ne laser (L), dexamethasone (D), D + L, celecoxib (X), and X + L. D and X were injected im at doses of 5 and 22 mg/kg, respectively, 24 h before the experiment. A 1-cm long surgical wound was made with a scalpel on the abdomens of the mice. Animals from gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
0
21
0
6
Order By: Relevance
“…After analyzing different wavelengths and energy doses applied to fibroblast cells, it was found that the highest number of mitoses was reached with a dose of 15 J/cm 2 and that above 60 J/cm 2 there was a reduction in cell division (20,21). According to Meirelles et al (2), marked maturation of granulation tissue is found on the 21st day of treatment using the energy density of 20 J/cm 2 at 660 and 780 nm.…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing different wavelengths and energy doses applied to fibroblast cells, it was found that the highest number of mitoses was reached with a dose of 15 J/cm 2 and that above 60 J/cm 2 there was a reduction in cell division (20,21). According to Meirelles et al (2), marked maturation of granulation tissue is found on the 21st day of treatment using the energy density of 20 J/cm 2 at 660 and 780 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of all skin lesions were collected in a way that included part of the skin adjacent to the sutured edges of the incisional wound and all the scar tissue in depth. 2,12,20 The samples of the skin lesions obtained were fixed in paraformaldehyde-10% (p H 7.0) for at least 24 hours. After fixation, the samples were gradually dehydrated in increasing concentrations of ethanol (70% to 100%), cleared in xylene, and embedded in paraffin in accordance with routine histological methods.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the study, ten pairs of images were filed, totaling 50 histological sections, which were subjected to counting the volume fraction (mm 2 ) of keratinocytes (keratinization) and epithelium (epithelialization) using digital marking by color contrast. 2,20 Initially, we performed an ideal estimate for sampling using Statemat ® 2.0 software, with test power of 90% and alpha error of 0.05, which indicated five animals per group, totaling 20 experimental animals. In the evaluation of data, we performed a normality test (Shapiro-Wilk) and one-way analysis of variance (ANOVA), followed by the nonparametric test of Mann-Whitney U, using Prism ® 5.0 software (GraphPad, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations